Development of a Pancasila Education Teaching Module with Integration of Mattabe’ Culture for Strengthening Student Character Values - ., Sudarmin; ., Munirah; ., Sukmawati (Journal of Ecohumanism, 2024)
This study aims to develop and analyze a Pancasila education teaching module that incorporates the local Bugis-Makassar culture for elementary schools. It using the ADDIE development model, the research findings indicate that the Pancasila education teaching module meets the established criteria. The content effectively reflects Pancasila values integrated with Mattabe’ culture, aligns with the Merdeka curriculum, and expert feedback confirms that the module is relevant and ready for use in teaching. The study concludes that the Pancasila education module presents accurate and authentic content, uses simple language, and employs interactive, engaging, and contextual teaching methods. Expert validation confirms that the module is ready for implementation in educational settings.Pancasila Education Teaching Module